Effectiveness of NPIs and vaccine coverage in the prevention and control of COVID-19 epidemic - an ecological comparative study among Australia, Korea, Singapore, Israel and India - Wen-xin YAN; Zheng ZHU; Yun-xiao WU (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo compare measures and effectiveness of case detection, transmission control, and vaccination for containment of coronavirus disease 2019 (COVID-19) epidemic in Australia, South Korea, Singapore, Israel, and India for providing evidences to the development of strategies on worldwide prevention and control of the epidemic. MethodsThe data on COVID-19 epidemic from January 1st 2020 through 2021 in the five countries were retrieved from the website of Our World in Data. Country-specific effects of non-pharmacological interventions (NPIs) and vaccinations on infectious source tracing, intercepting transmission, and protecting susceptible populations in the five countries were assessed by comparing correlations between the daily numbers of testing and incidence cases, the Oxford-stringency index and daily incidences, and the number of fully vaccinated persons per 100 population and daily mortalities. ResultsThe severity of COVID-19 epidemic was controlled by increased daily number of detection in a certain extent and the daily number of confirmed incidence cases decreased after the day with the highest detection number. The Oxford-stringency index increased with the worsening of COVID-19 epidemic but decreased somewhat with the weakening of the epidemic and the decrease in the index could relate to a rebound of the epidemic. The case-fatality rate of COVID-19 decreased with the increase of fully vaccination rate. ConclusionCountries around the world should actively learn from international experience, follow the laws of epidemiology, start from controlling the source of infection, cutting off the transmission route and protecting susceptible people, adapt NPIs and promote booster vaccination universally, further research and development, for coping effectively with the global public health challenge.